TRADITIONAL, COMPLEMENTARY AND ALTERNATIVE MEDICINE USE IN A COMMUNITY POPULATION IN LAO PDR - Peltzer, Karl; Sydara, Kongmany; Pengpid, Supa (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: The aim of this study was to assess the prevalence and associated factors of Traditional, Complementary and Alternative Medicine (TCAM) use in a community setting in a central province of Lao PDR. Materials and Methods: A cross-sectional community survey in 4 urban and 4 rural districts was conducted with the International Complementary and Alternative Medicine Questionnaire (I-CAM-Q). Results: Of the 1600 participants in the survey, the overall prevalence of any TCAM use (providers, products or self-care) was 40.2% (TCAM provider= 14.8%, TCAM products=34.1%, and self-help TCAM=4.5%) in the past 12 months.The most frequently used herbal medicines were Maringa pterygosperma (12.6%), followed by Curcuma longa L. (9.4%), Curcuma xanthorrhiza (9.4%) and Centella asiatica (7.2%). Many of the TCAM products were used for the purpose of health tonic or nourishments and for a number of chronic conditions (gout, dyslipidaemia, hypertension, diabetes, asthma, cancer, migraine, mental disorder, and gastrointestinal disorders). In multivariate logistic regression, lower educational level, rural residence and having chronic conditions was associated with any TCAM use. Conclusions: TCAM use seems to be common in Lao PDR and better knowledge on the use of different TCAM modalities in this population may improve patient management.